Animal Husbandry - Kukovics, Sándor (IntechOpen, 2022)
This volume presents selected issues in the complex and diverse science of animal husbandry. The use of computer programs provides an opportunity to improve breeding and optimize farm management. At the same time, the use of traditional breeding methods is also of decisive importance. Knowledge of animal welfare and animal wellness is of great help in controlling animal health issues and in economic production. In the biological processes of reproduction of dairy cows, the events of the 100 days after calving are of fundamental importance. Production systems influence the process of product production, in which the relationship between animal products and human health goes far beyond animal husbandry, and to which the issue of greenhouse gases is also connected. The quality of manufactured meat products is influenced by both on-farm and off-farm factors, but good meat cannot be produced from low-quality animals, even with excellent slaughterhouse work. Background knowledge of animal health ‒ including the microbiome in the digestive tract, which makes use of the feed ‒ makes this activity more effective, which is of particular importance in the case of broiler chickens. Knowing the behavioural characteristics of animals (rams) enables better management. Many horse breeds are capable of artificial gaits as a result of breeding and selection processes. Comparative knowledge of the movements of these horse breeds also helps to understand their differences. The quality of life of animals and the quality of manufactured products are also affected by polycyclic aromatic hydrocarbons from the environment, which, being stored and enriched in fat-containing tissues, can also have adverse effects on the human consumer. Each topic presented not only offers specialist knowledge but makes interesting reading in its own right.